Difficult Heritage. The Experience of the Fossoli Camp Foundation - Luppi, Marzia; Schintu, Francesca (Ex Novo: Journal of Archaeology, 2021)
The historic site of Fossoli Camp is a unique stone witness which still bears the marks left by the central years of the twentieth century. During the Second World War it was a national camp for racial and political deportees, but its story extends to the 1970s when it was used to house civilian orphans and refugees. Today it is a place where history blends with experience and education. The primary goal of the Fossoli Foundation is the protection and preservation of the Camp’s heritage, together with its enhancement through activities including research, documentation, and education to promote cultural awareness. The Foundation focuses especially on close co-operation with schools, developing targeted educational projects and pathways for both students and teachers, with organised visits to its own memorial sites and other European ones. European projects and partnerships represent an increasing part of its activities, and the Foundation is now a member of several national and international networks.